Two new species of Brontostoma Kirkaldy (Hemiptera: Heteroptera: Reduviidae: Ectrichodiinae) from Bolivia, with description of the male genitalia of two other species of the genus, and description of the female of B. doughertyae Gil-Santana, Lopes, Marques & Jurberg - Gil-Santana, Hélcio R.; Baena, Manuel (Zootaxa, 2009)
Brontostoma deferreri sp. nov. and Brontostoma diringshofeni sp. nov. from Bolivia are described. The female of B. doughertyae Gil-Santana, Lopes, Marques & Jurberg, 2005, is described together with comments on the variation of coloration in the male of the same species, as well as a short description of the male genitalia. The male genitalia of B. basalis (Stål, 1859) are also described.